2017
DOI: 10.1016/j.chemosphere.2017.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Extending the functionality of the slurry ferrihydrite-DGT method: Performance evaluation for the measurement of vanadate, arsenate, antimonate and molybdate in water

Abstract: The monitoring of oxyanions in waters, presents significant challenges due to their relatively low concentrations, and a characteristically changeable/unstable/reactive geochemistry with high spatial and temporal turnover. This results in a very heterogeneous pattern of mobility and bioavailability, which is difficult to capture reliably and in a cost effective manner. The diffusive gradients in thin-films (DGT) technique is a popular analytical tool for testing water quality, primarily because it provides a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…For total As, numerous studies have shown that the DGT performances of the 3MP, Fh, Metsorb ® , and/or ZrO2 binding gels were comparable in laboratory over 40 -120 h of deployment in freshwater[3,9,12,41,42], similarly to what has been observed in the present study. On the contrary, in binding gels up to 40-96 h of deployment time.…”
supporting
confidence: 90%
“…For total As, numerous studies have shown that the DGT performances of the 3MP, Fh, Metsorb ® , and/or ZrO2 binding gels were comparable in laboratory over 40 -120 h of deployment in freshwater[3,9,12,41,42], similarly to what has been observed in the present study. On the contrary, in binding gels up to 40-96 h of deployment time.…”
supporting
confidence: 90%
“…For this reason, it is used and widely studied as model material to elucidate the adsorption of cations, anions, and organic matter. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The surface area of ferrihydrite is an essential characteristic particularly from the perspective of surface complexation modelling. One reason is that ferrihydrite particles are usually charged.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in situ techniques for measuring phosphorous needs to developed. Diffusive Gradient in Thin Film (DGT) technique has been developed for in situ measurements of vanadate, arsenate, antimonate, and molybdate in water [14], methyl mercury in rice plants [15], reactive phosphorus species in natural water, sediment and soil [16] and others. The principle of phosphate measurement using the DGT technique is based on the diffusion of phosphate species through the polyacrylamide gel layer and then bound by the ferrihydrite layer embedded in the next gel layer [17].…”
Section: ■ Introductionmentioning
confidence: 99%